PENGEMBANGAN MODUL PEMBELAJARAN DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN KRITIS SISWA MATEMATIKA DI SD N 2 PEDES - Maria Margaretha; Heru Purnomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of a deep learning–based instructional module aimed to enhance third-grade students’ critical reasoning skills in mathematics, specifically on multiplication material at SD Negeri 2 Pedes. This study sought to analyze the feasibility, practicality, and effectiveness of the developed module in improving students’ critical reasoning abilities at the elementary school level. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 17 third-grade students of SD Negeri 2 Pedes. The research instruments included expert validation sheets (material experts and module experts), teacher and student response questionnaires, and pretest–posttest instruments. The data were analyzed using descriptive quantitative techniques to determine the level of validity, practicality, and effectiveness of the module.The results indicated that the module achieved a feasibility percentage of 85% from the material expert and 80% from the module expert, both categorized as highly feasible. The responses from the teacher and students in the field trial reached 86.66% and 80%, respectively, which were categorized as highly practical. In terms of effectiveness, the students’ average score increased from 67.35 in the pretest to 83.82 in the posttest, with an N-Gain value of 0.4595 (moderate category). These findings demonstrate that the deep learning–based instructional module is feasible, practical, and effective in enhancing third-grade students’ critical reasoning skills in multiplication material at the elementary school level.Top of Form